2020
DOI: 10.22271/chemi.2020.v8.i5d.10539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IPM modules against shoot and fruit borer in Okra

Abstract: Okra (Abelmoschus esculentus) locally known as 'Bhendi' or 'Dherosh' also known as lady's finger is a popular and most common annual vegetable crop grown from seed in India and in other tropical and subtropical parts of the world. Several insect pests have so far been recorded to attack okra but okra shoot and fruit borer, is the most destructive insect pest responsible for considerable damage inflicting yield loss up to 40-50% or more. Now-a-days, IPM has been attaining immense importance in the agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The chemical module was found toxic to the Coccinellids recording least population of the grubs. The present investigations are in agreement with the findings of Patil et al (2019) and Patil et al (2020). Similarly, Ingale (2016), Boraste (2019), Naik et al (2019) also observed that the pongamia oil was not toxic to adult coccinellid predators.…”
Section: Resultssupporting
confidence: 93%
“…The chemical module was found toxic to the Coccinellids recording least population of the grubs. The present investigations are in agreement with the findings of Patil et al (2019) and Patil et al (2020). Similarly, Ingale (2016), Boraste (2019), Naik et al (2019) also observed that the pongamia oil was not toxic to adult coccinellid predators.…”
Section: Resultssupporting
confidence: 93%